1993
DOI: 10.1128/jvi.67.11.6698-6706.1993
|View full text |Cite
|
Sign up to set email alerts
|

Central neuropathogenesis of vesicular stomatitis virus infection of immunodeficient mice

Abstract: To determine whether central neuropathogenesis associated with vesicular stomatitis virus (VSV) infection is regulated by T cells, we have examined the effects of intranasal infection of mice lacking T cells. The mice examined were of two kinds: (i) thymus-deficient BALB/c nulnu nice and (ii) BALB/c mice experimentally depleted of T cells by systemic infusions of a monoclonal antibody to the CD4 or CD8 cell surface molecules. These mice were infected intranasally with a single dose of replication-competent VSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 36 publications
1
61
0
Order By: Relevance
“…While mice are not considered a natural host for VSV, they have been used as an animal model for studying VSV pathogenesis for over 70 years [38]. The exquisite sensitivity of mice to VSV infection has proven them as a valuable research tool for assessing virulence of wild type and attenuated strains of VSV [12][13][14][15][16][17][18][19][20]. While the neurovirulence associated with VSV infection in mice has been well studied, there has not been much advancement in the understanding of the biodistribution of VSV in mice since the pioneering work of Sabin and Olitsky in the 1930s [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While mice are not considered a natural host for VSV, they have been used as an animal model for studying VSV pathogenesis for over 70 years [38]. The exquisite sensitivity of mice to VSV infection has proven them as a valuable research tool for assessing virulence of wild type and attenuated strains of VSV [12][13][14][15][16][17][18][19][20]. While the neurovirulence associated with VSV infection in mice has been well studied, there has not been much advancement in the understanding of the biodistribution of VSV in mice since the pioneering work of Sabin and Olitsky in the 1930s [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…VSV infection of humans is typically either asymptomatic or causes a mild influenza-like illness [6]. Among small mammals, mice are readily infected experimentally via a variety of inoculation routes and thus have served as a tractable model for immunogenicity, pathogenicity, neurotropism and neurovirulence studies [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Infiltration of CD4 ϩ and CD8 ϩ T cells into the CNS has been observed in various models of neurotropic virus infection in rodents (6,11,42,46,73). It has been stated that in general, CD4 ϩ cells largely determine the protective immune response to viral infection of the brain (62), although a role for CD8 ϩ cells has been documented in some cases (6,21,28,65,72). It is also known that T cells can generate an immunopathologic response, depending on the type of infecting virus, (57,66,71).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we observed that the absence of pDCs resulted in a moderate but significant decrease in the numbers of OVA-specific CD8 + T cells, whereas the generation of plasma cells and production of virus-specific antibodies were unaffected. Although the reduction in antigen-specific CD8 + T cells had a modest impact on viral titers and survival, previously published data have illustrated that antibody responses are necessary and sufficient for VSV eradication, whereas a CTL response is not essential for VSV clearance but provides limited help to control viral spread (119).…”
Section: Pdcs Enhance Anti-vsv Cd8 + T-cell Responses In Vivomentioning
confidence: 96%